Selective Attention in Exchange Rate Forecasting - Svatopluk Kapounek; Zuzana Kucerova; Evzen Kocenda (Charles University in Prague, Institute of Economic Studies (IES), 2020)
We analyze the exchange rate forecasting performance under the assumption of selective attention. Although currency markets react to a variety of different information, we hypothesize that market participants process only a limited amount of information. Our analysis includes more than 100,000 news articles relevant to the six most-traded foreign exchange currency pairs for the period of 1979-2016. We employ a dynamic model averaging approach to reduce model selection uncertainty and to identify time-varying probability to include regressors in our models. Our results show that smaller sizes models accounting for the presence of selective attention offer improved fitting and forecasting results. Specifically, we document a growing impact of foreign trade and monetary policy news on the euro/dollar exchange rate following the global financial crisis. Overall, our results point to the existence of selective attention in the case of most currency pairs.
Keywords: F33; G41; C11; 330; exchange rate; selective attention; news; forecasting; dynamic model averaging